The methodology of Abu 'Isaa Al-Warraq in the study of christianity with special reference to his kitab al-Radd ‘ala al-Thalath Firaq min al-Nasara - Shehu, Fatmir Mehdi (2019)
This paper seeks to examine the methodology of Abu ‘isa al-Warraq, the classical Muslim scholar, in the study of Christianity with special reference to his master piece al-Radd ‘Ala al-Thalath Firaq Min al-Nasara. The aim of this research is to investigate al-Warraq’s polemical discourse consisting of arguments, disputes and refutation, while responding to the three Christian sects, Malkiyyah (Melkites), Nasturiyyah (Nestorians) and Ya'qubiyyah (Jacobites) in relation with the concept of Trinity. This research is very significant as it suggests new insights for young scholars and students of religious studies in dealing with Christian doctrine of trinity as addressed by the content of al-Warraq’s original script. This study discusses: (1) Abu ‘Isa al-Warraq’s brief chronology, (2) his selected work(s) on the study of religion, and (3) his methodology in the study of Christian doctrine of trinity through selected statements from the original work. Descriptive and analytical methods are employed in this study. The expected findings of this scientific study will add to contemporary scholarship of comparative religion the insights of the original work of a Muslim polemicist in the study of Christianity. It will as well, enhance the understanding of contemporary Muslim approaches to the study of other religions in general, and Christianity in particular.